Application of Fuzzy Logic in Motorcycle Security Systems Based on Internet of Things (IoT) - Zulfahmi Syahputra; Arpan; Mohammad Faiza Zachary (INFOKUM, 2021)
The development of motorcycle use in Indonesia is increasing every year. This increasing trend is also accompanied by the increasing number of theft crimes of motorcycles. This is due to the physical nature of the motorcycle which is relatively small and easy to steal. In this study the author will discuss the motorcycle theft prevention system by installing various sensors built using fuzzy logic and utilizing the concept of the Internet of Things (IOT). This fuzzy logic consists of values and domains that are classified into several variables to conclude the degree and status of the motorcycle as an alarm trigger. Then by utilizing IOT the alarm is converted into a notification that will be sent via the motorcycle user's Telegram application if the motorcycle is stationary, Bergerak or moved. This system has 2 (two) components, namely hardware in the form of several sensors including infrared sensors along with a microcontroller and software connected to the Telegram application which functions as a motorcycle status notification receiver.